Factors Influencing Health Equity of Influenza Vaccination in Pediatric Patients. Issue 2 (March 2022) - Donnelly, Lane F.; Wood, Matthew; Chantra, Jean; Loh, Ling; Burkart, Brendan; Lee, Grace M.
Abstract : Introduction: Social factors can be a determinate for multiple health outcomes. We evaluated the association of numerous social factors on rates of influenza nonvaccination in a large pediatric primary and subspecialty care system. Methods: During the 2019–2020 influenza vaccination season, we calculated the nonvaccination rate for a pediatric healthcare system with both subspecialty and primary care practices. We compared influenza vaccination rates for factors that might affect health equity (patient gender, language preference, health insurance payer category, race and ethnicity, and estimated median household income based on zip code analysis) by creating simultaneous 95% confidence intervals using the Wilson method with continuity correction and a Bonferroni adjustment for the number of categories compared. Results: The overall influenza nonvaccination rate was 58.0% (59, 375 not vaccinated of 102, 377). Statistically significant differences in nonvaccination rate were present for the following health equity indicators: Spanish (75.6%) and Chinese Dialects (78.0%) > English (55.9%) speaking; Hispanic (70.1%) > many other race and ethnicities; Asian (51%) < many other race and ethnicities; Commercial (53.5%) < Public (71.2%) or Self (81.4%) pay; and lower (67.6%–79.1%) > higher median household income (52.9%–56.4%). Conclusions: Non-English language preference, Hispanic ethnicity, public insurance, and lower median household income are associated with a decreased likelihood of influenza vaccination. We are using these data to inform our key drivers to improve influenza vaccination in our system.